Effects of intrathecal and intracerebroventricular microinjection of kaempferol on pain: possible mechanisms of action - Sajjad Jabbari; Maryam Bananej; Mohammad Zarei; Alireza Komaki; Ramin Hajikhani (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Kaempferol (KM), a flavonoid, has an anti-inflammatory and anticancer effect and prevents many metabolic diseases. Nonetheless, very few studies have been done on the antinociceptive effects of KM. This research aimed at assessing the involvement of opioids, gamma-aminobutyric acid (GABA) receptors, and inflammatory mediators in the antinociceptive effects of KM in male Wistar rats. Experimental approach: The intracerebroventricular and/or intrathecal administration of the compounds was done for examining their central impacts on the thermal and chemical pain by the tail-flick and formalin paw tests. For assessing the role of opioid and GABA receptors in the possible antinociceptive effects of KM, several antagonists were used. Also, a rotarod test was carried out for assessing motor performance. Findings/Results: The intracerebroventricular and/or intrathecal microinjections of KM (40 μg/rat) had partially antinociceptive effects in the tail-flick test in rats (P < 0.05). In the formalin paw model, the intrathecal microinjection of KM had antinociceptive effects in phase 1 (20 and 40 μg/rat; P < 0.05 and P < 0.01, respectively) and phase 2 (20 and 40 μg/rat; P < 0.01 and P < 0.001, respectively). Using naloxonazine and/or bicuculline approved the involvement of opioid and GABA receptors in the central antinociceptive effects of KM, respectively. Moreover, KM reduced the expression levels of caspase 6, interleukin-1β, tumor necrosis factor-α, and interleukin-6. The antinociceptive effects of KM were not linked to variations in the locomotor activity. Conclusion and implications: It can be concluded that KM has remarkable antinociceptive effects at a spinal level, which is associated with the presence of the inflammatory state. These impacts were undetectable following injections in the lateral ventricle. The possible mechanisms of KM antinociception are possibly linked to various modulatory pathways, including opioid and GABA receptors.